(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Fossil fuels are the chief contributors to urban air pollution and major source of green house gases and considered the prime cause behind the global climate change. With the increasing fuel prices, the auto industry forced to make their engines to breathe cleanly and fuel efficiently. Biodiesel is a renewable diesel fuel substitute that can be made by chemically combining any natural oil or fat with an alcohol such as methanol or ethanol. Some of the well-known liquid biofuel are ethanol for gasoline engines and biodiesel for compression ignition engines or diesel engines. Biodiesel is a renewable and environmental friendly alternative diesel fuel for diesel engine. It can be produced from food grade vegetable oils or edible oils, nonfood grade vegetable oils or inedible oil, animal fats and waste or used vegetable oils, by the transesterifcation process. Transesterifcation is a chemical reaction in which vegetable oils and animal fats are reacted with alcohol in the presence of a catalyst. The products of reaction are fatty acid alkyl ester and glycerin, and where the fatty acid alkyl ester known as biodiesel. Biodiesel is an oxygenated fuel containing 10% to 15% oxygen by weight. Using biodiesel can help to reduce the world’s dependence on fossil fuels and has significant environmental benefts. The reasons for these environmental benefits using biodiesel instead of the conventional diesel fuel reduces exhaust emissions such as the overall life circle of carbon dioxide (CO2), particulate matter (PM), carbon Monoxide (CO), sulfur oxides (SOx), volatile organic compounds (VOCs), and unburned hydrocarbons (HC) significantly. Furthermore, since biodiesel can be said a sulfur-free fuel, it has 99% less SOx emission than the diesel fuel. However, most of the biodiesel produce 10% to 15% higher oxides of nitrogen (NOx) when fueling with 100% biodie-sel for a cleaner air and cleaner environment. They are technically competitive with and offer technical advantages compared to petroleum-diesel fuel. Aside from being renewable and biodegradable, biodiesel reduces most emissions while engine performance and fuel economy are nearly the same as the conventional fuel. In this paper author have discussed various merits and de-merits of biodiesel on the environment used as C.I.Engine fuel. Key words: Biodiesel; CO2 emission; Global warming; Emission reduction DOI: 10.3126/hn.v7i0.4240 Hydro Nepal Journal of Water, Energy and Environment Vol. 7, July, 2010 Page: 65-70 Uploaded date: 31 January, 2011